Efficacy and safety of prostaglandins vs double balloon catheter in inducing labor: a meta-analysis - Chong, Jia S.; Chew, York L.; Fernando, Ayendra; Nalliah, Sivalingam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: To compare the efficacy and safety of double‐balloon catheter with prostaglandin E2 (PGE2) in induction of labor. Methods: We searched electronic sources from Medline, Scopus, PubMed, Science Direct and Cochrane Library Database of Systematic Reviews. Only randomized controlled trials and observational studies comparing the PGE2 agents with double-balloon catheter for cervical ripening and labour induction in women with unfavorable cervix were included in the analysis. The main outcomes included vaginal delivery rate within 24 hours and cesarean delivery rates. We calculated relative risks and mean differences using fixed effects and random‐effects models. Results: Prostaglandin was more favourable for vaginal delivery within 24 hours compared to double balloon catheter, but was not statistically significant (RR 1.17: 95% CI 0.96-1.42 p =0.12). The induction to delivery time yielded a non-significant result that again favors prostaglandin (SMD 0.02 CI:0.18,0.22, p = 0.86). There was no significant difference in the cesarean delivery rates between the two groups (RR 1.02: 95% CI 0.92-1.14, p = 0.68). Uterine hyperstimulation and Neonatal Intensive Care Unit (NICU) admissions were significantly higher with prostaglandin. (RR 0.09: CI 0.04, 0.22 p<0.00001 and RR 0.75 CI: 0.62,0.90 p=003). Conclusions: There is no significant difference in the success of induction of labour between use of PGE2 and double balloon catheter. Uterine hyperstimulation and NICU admissions were significantly higher in Prostaglandin group.